Digital Transformation in Tourism and Hospitality Management in Vietnam: Opportunities, Challenges, and Solutions - Hue, Nguyen Thi; Phuong, Luu Thi Mai (International Journal of Scientific Research and Management (IJSRM), 2025)
In the era of rapid technological advancement and the Fourth Industrial Revolution, digital transformation has emerged as a critical driver reshaping industries across the globe, including the tourism and hospitality sector. For Vietnam - a country rich in cultural heritage and diverse natural landscapes - tourism and hospitality hold strategic economic significance. In this context, digital transformation refers to the integration of digital technologies into all aspects of tourism operations, leading to fundamental changes in how businesses operate and create value for customers. This paper aims to explore the multidimensional nature of digital transformation in Vietnam's tourism and hospitality industry. Specifically, the study analyzes current trends, assesses the level of digital technology adoption among enterprises, identifies key opportunities and challenges, and proposes strategic solutions to accelerate the digital transformation process. By situating the issue within Vietnam’s socio-economic landscape, the paper offers valuable insights for policymakers, industry leaders, and the academic community to foster sustainable and inclusive digital growth in this sector.